Trends in sustainability disclosures in the integrated reports of South African listed companies - Herbert, Shelly (College of Accounting, 2019)
Over the last 30 years organisations have increased their sustainability disclosures in response to an increased focus on corporate sustainability, which considers the economic, environmental, and social aspects of an organisation. With the introduction of integrated reporting, organisations are encouraged to use integrated thinking to create value for their organisation in the short and long term, using all of the capitals or resources available to them. The new emphasis on reporting on maximising the organisation’s human, social and relationship capital, along with its natural capital echoes the focus of sustainability reporting. However, the objectives of integrated and sustainability reporting differ in their focus, between a focus on shareholders and value creation, compared to a focus on the organisation’s impact on the environment, society, and the economy. This exploratory study examines trends in sustainability disclosure in the integrated reports of South African listed companies. It explores the trends in companies’ sustainability information in their integrated reports from 2011, when integrated reporting became mandatory in South Africa, following the implementation of the King Code of Governance Principles (King III) of 2009. It covers reporting up to 2015, when the 2013 International Integrated Reporting Framework (the Framework) of the International Integrated Reporting Council was adopted in South Africa. It also takes into account the 2013 G4 Guidelines of the Global Reporting Initiative. Interpretive content analysis is used, which involved creating a disclosure checklist based on the disclosure categories outlined in the G4 requirements. Issues relating to Broad-based Black Economic Empowerment ('BBBEE’) which are specific to South Africa were included in the disclosure checklist. This study does not seek to measure compliance with the requirements of the GRI, or the quality of the sustainability disclosures, but rather uses the requirements as a guide for sustainability disclosures that could be included in the integrated reports of South African companies. Statistical techniques were then used to determine if significant trends in disclosure were observable in the integrated reports from 2011 to 2015. The results show that there was a notable change in how sustainability disclosures are presented in the integrated reports, although there is no meaningful change in the number and type of sustainability disclosures. Industry classification, and the age and size of companies were also found to be significant in the quantity and quality of sustainability disclosures observed. This study provides insight into the integrated and sustainability disclosure practices of South African listed companies. It also examines their compliance with the guidance provided in the Framework relating to the preparation of fully integrated reports.